Aged rats under zoledronic acid therapy and oral surgery - Matsumoto, Mariza Akemi [UNESP]; de Abreu Furquim, Elisa Mara [UNESP]; Gonçalves, Alaíde [UNESP]; Santiago-Júnior, Joel Ferreira; Saraiva, Patrícia Pinto; Cardoso, Camila Lopes; Munerato, Marcelo Salles; Okamoto, Roberta [UNESP] (Elsevier, 2017)
Introduction Aging brings a number of health conditions that can compromise the healing process in elderly individuals, significantly when it comes to bone tissue. The aim of the present study was to analyze the effects of zoledronic acid (ZL) therapy on socket healing of aged male rats. Materials and methods Twenty-four Wistar male rats, 20 months old, underwent surgical procedures for the extraction of the upper right incisor and were divided into two groups according to the treatment: Control (C) – intravenous (IV) 0.9% saline, ZL – 0.035 mg/kg of IV zoledronic acid, both every 15 days. At the fifth dose of both substances, tooth extractions were performed and the animals were euthanized after 14 and 28 days. Results IV administration of ZL caused OPG-RANKL system imbalance, resulting in deficient bone formation and remodeling and alteration of osteoclast morphology, as well as maintaining persistent inflammation during the healing period. Conclusions IV administration of ZL delayed extracted dental socket healing of aged rats, but not enough to cause osteonecrosis, raising a question about different responses to IV BP therapy considering animal age.
Keywords: Aging; Bisphosphonate; Oral surgery; Rats